PEMBIAYAAN UMKM, KINERJA BANK SYARIAH DAN PERTUMBUHAN EKONOMI DI INDONESIA - Iwan Setiawan (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2021)
Sharia banks have an important role to do with the development of MSMEs and the economy in Indonesia. The share of sharia bank financing in MSMEs decreased beyond the minimum limit set. This study aims to look at the role of MSME financing on the performance of Sharia banks and economic growth in Indonesia. The study used monthly data for the period 2016-2019 with the two stage least square (TSLS) analysis method. The results of this study revealed that financing in MSMEs contributes greatly to the improvement of the performance (ROA) of Sharia banks. The financing of MSMEs of Sharia banks does not contribute directly to economic growth. The contribution of MSME financing to economic growth occurs through the role of profit (ROA) of Sharia banks. There is a two-way relationship and mutual influence between sharia bank profits and economic growth. The role of economic growth towards bank profits is greater than the role of sharia banks in economic growth. It is important to pay attention to the portion and quality of financing in MSMEs that can improve the performance of Sharia banks and at the same time boost economic growth in Indonesia.